Entrepreneurial Self-Efficacy and Transaction Frequency: An Extension of the Expectation-Confirmation Model in MSMEs - Basbeth, Firdaus; Nardo, Rio (Jurnal Minds: Manajemen Ide dan Inspirasi, 2026)
This study examines how entrepreneurial self-efficacy (ESE) shapes MSMEs’ continuance intention to use QRIS within the Expectation Confirmation Model under increasing digital payment adoption. It advances ECM by demonstrating a boundary condition where transaction frequency fails as a moderator, repositioning satisfaction as the dominant post-adoption mechanism over behavioral intensity. Using survey data from 150 MSMEs in Indonesia and SmartPLS4 analysis, the results show that ESE enhances perceived usefulness, which significantly drives continuance intention through satisfaction, while transaction frequency is insignificant. These findings support habit formation and technology embeddedness perspectives, indicating that repeated use loses explanatory power once usage stabilizes. Continuance decisions are therefore primarily affect-driven rather than behavior-driven. The study implies that policymakers and fintech providers should prioritize system reliability and user satisfaction rather than merely increasing transaction frequency to sustain QRIS adoption.